Women’s Work and its Impact on Family Roles (A Field Social Study in the City of AlDiwaniyah) - Salam Miri, Baidaa; Raheem Kadhim, Thaer (International Journal of Psychosocial Rehabilitation, 2020)
When family is well-being, the entire society is reformed, especially the mother or wife. The family is considered the natural environment and the suitable ground for the growth and building of the individual personality of the child. Yet the spread and availability of education for women makes her get work that affects her family life by performing other roles besides her main role as a mother and housewife. As such, many problems have resulted because of the conflicting roles of the domestic roles and the roles of the new work. The current study deals with the effects that are generated from women’s work that influence, in one way or another, their family roles as wives, mothers, or housewives. So that the woman’s work is seen through its effect on other parties like the husband or children. Generally, the value of any research lies in its benefit after conducting it scientifically. Accordingly, the main goal of the research is to discover and find out the reasons that prompted the woman to work. As well, it aims at knowledge of the positive and negative aspects of her work on her family members. So the research form is distributed on a sample consisting of (225) surveyed women working in the city of Diwaniyah, in which the social survey methodology is used in addition to the questionnaire form as a basic method for collecting the statement. Then, it is concluded some results, the most important of which are: The economic factor is at the forefront of the reasons that pushed women to enter the field of work outside the home and compete with men for social and psychological reasons, and work has many effects on the woman herself and her family.